3x + 5 > 11
3x + (5 - 5) > 11 - 5
3x > 6
3x / 3 > 6 / 3
x > 2
x - 3 < 1
x (-3 + 3) < 1 + 3
x < 4
When subtracting / adding values to both sides, the inequality does not change.
When multiplying / dividing by a positive value, the inequality also doesn't change, but when multiplying , dividing with a negative value, the inequality must be flipped.
Answer:
son's present age = 30
father's present age=60
Step-by-step explanation:
his son's present age = x years
his father's present age = 2x years
before 20 years his son's age=(x-20) years
before 20 years father's age=(2x-20) years4(x-20)=(2x-20)
4x-80=2x-20
4x-2x=80-20
2x=60
x=30
Hey smart cookie ;)
So with this all we need to do is factor the expression.
Our answer is going to be 2x(16x^4+15)
Let me know if you have other questions!
Have a terrific day.
~Brooke❤️
Answer:
False (under assumption T(2,-3) means move it right 2 units and down 3 units).
Step-by-step explanation:
The statement is false.
T(2,-3) means move the point right 2 (so plus 2 on the x-coordinate) and down 3 units (so minus 3 on the y-coordinate).
So (1,6) will become (1+2,6-3)=(3,3) after the translation.
The point (1,12) will become (1+2,12-3)=(3,9).
If the statement were "Under the translation T(2,-3) the point (1,12) will become (3,9)", then it would be true.
Or!
If the statement were "Under the translation T(2,3) the point (1,6) will become (3,9)", then it would be true.
Answer:
n=6
Step-by-step explanation:
(n-18)/3 = -4
multiply by 3
n-18 = -12
add 18
n = 6